Composition and application of anti-aging organic silicon pressure-sensitive adhesive
By using structurally symmetric branched vinyl silicone oil to optimize the formulation of silicone pressure-sensitive adhesive, a more stable crosslinking network is formed, which solves the problems of high adhesion climb rate and high crystal point rate of the film surface, and achieves better aging performance and crystal point control.
Patent Information
- Application Number
- CN202510003899.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-02
AI Technical Summary
During the application process, existing silicone pressure-sensitive adhesives have problems such as high adhesion climb rate and high membrane surface crystal point rate, especially in the field of electronic applications, which may lead to damage to the paste.
Structurally symmetric branched vinyl silicone oil is used to form a tighter and regular crosslinking network by adjusting the vinyl content and viscosity, reducing the crosslinking density of the adhesive film, improving adhesion stability, and reducing the formation of crystal points on the film surface by optimizing the formulation.
In the application scenario where the adhesion range is 0 to 100g/inch, the adhesion climb rate of high temperature and high humidity aging is achieved with an adhesion climb rate of ≤50%, the maximum crystal point size of the film surface does not exceed 100μm, and the crystal point ratio is ≤1000 pieces/m2, which significantly improves the aging performance and crystal point problems of the adhesive film.
Smart Images

Figure BDA0005226300750000021 
Figure BDA0005226300750000031 
Figure BDA0005226300750000041
Abstract
Description
Technical Field
[0001] The invention belongs to the field of organic silicon, and in particular relates to the composition and application of an aging-resistant organic silicon pressure-sensitive adhesive. Background Art
[0002] Silicone pressure-sensitive adhesive has the advantages of low curing temperature and no by-products, and is widely used as a protective film in the fields of process protection and shipment protection. The curing mechanism of silicone platinum pressure-sensitive adhesive is a silane-hydrogen addition reaction, that is, the vinyl functional group reacts with the silicon-hydrogen bond to form a cross-linked network. The common silicone platinum pressure-sensitive adhesive formula is basically a linear polymer, and the cross-linking points formed are limited. The organic silicone film formed has good initial adhesion and high adhesion, but as time goes by, the adhesion of the film to the adherend will increase. Depending on the application scenario, there are different requirements for the application performance of silicone pressure-sensitive adhesives, and some applications have higher requirements for the aging climb rate of silicone pressure-sensitive adhesives. After the process protection is completed, especially in the field of electronic applications, if the adhesion climbs too high, the adhered object may be damaged during the removal of the protective film, causing losses. Usually, the formula of silicone addition type pressure-sensitive adhesive contains vinyl raw rubber, high viscosity vinyl silicone oil and MQ resin. The mixture of high molecular weight and high viscosity polysiloxane and MQ resin requires very high dispersion ability of the equipment. The resin and raw rubber that are not fully dissolved and dispersed in the high viscosity system are prone to form "crystal points" after the film surface is cured. The existence of crystal points may cause local stress concentration and affect the light transmittance of the film surface. Therefore, the silicone pressure-sensitive adhesive protective film used in the production process of 3C digital and other electronic products has high requirements for the crystal points on the film surface.
[0003] CN 114958295 A provides an ultra-low adhesion, low climb organic silicon pressure-sensitive adhesive and a preparation method and application thereof. The pressure-sensitive adhesive prepared by the invention is suitable for ultra-low adhesion application scenarios, that is, the application range of adhesion is 0 to 3 g / inch. In the application scenario of adhesion>3 g / inch, there is no technical invention to solve the low climb problem.
[0004] In summary, the current application field of addition-type silicone pressure-sensitive adhesives still has problems such as high adhesion climbing rate and high film surface crystal point rate, which need to be solved urgently. Summary of the invention
[0005] In order to solve the above technical problems, one of the purposes of the present invention is to provide an aging-resistant silicone pressure-sensitive adhesive, which can achieve an adhesion climbing rate of ≤50% under high temperature and high humidity aging of the silicone pressure-sensitive adhesive in the application scenario of an adhesion range of 0 to 100 g / inch, a maximum crystal point size of no more than 100 μm on the film surface, and a crystal point rate of ≤1000 / m2 for a randomly cut 1 cm×1 cm adhesive film observed under a 200-fold magnification microscope. 2 .
[0006] In order to achieve the above-mentioned invention object, this application adopts the following technical solution:
[0007] An aging-resistant silicone pressure-sensitive adhesive, comprising the following components in parts by weight:
[0008]
[0009] The inventors have discovered that a structurally symmetrical branched vinyl silicone oil can provide a tighter and more regular cross-linked network for the system during the curing process, improve the modulus and adhesion stability of the film, and in particular, the vinyl content of the branched vinyl silicone oil needs to be within a specific range. If it exceeds the specific range, the cross-linking density of the film will be too high, the initial viscosity will decrease, and the adhesion will be low, which cannot meet the needs of most application scenarios. While providing sufficient cross-linking functional groups, Q-type branched vinyl silicone oil has very good compatibility with the raw rubber and resin in the pressure-sensitive adhesive, and has a low viscosity. The viscosity at 25°C is only in the range of 200-600cP. Compared with the high-viscosity linear polysiloxane used in traditional silicone pressure-sensitive adhesives, it can make the pressure-sensitive adhesive system have better dispersion characteristics, which is conducive to the full dissolution of the pressure-sensitive adhesive composition in organic solvents, thereby greatly reducing the crystal point size and crystal point rate on the film surface.
[0010] The aging-resistant, low-crystal point rate organic silicone pressure-sensitive adhesive can achieve an adhesion climbing rate of ≤50% under high-temperature and high-humidity aging in an application scenario with an adhesion range of 0 to 100 g / inch, a maximum crystal point size on the film surface does not exceed 100 μm, and a randomly cut 1 cm×1 cm adhesive film is observed under a 200-fold magnification microscope, and the crystal point rate is ≤1000 / m 2 .
[0011] In one embodiment of the present application, the molecular weight of the vinyl-terminated raw rubber is 450,000 to 850,000, the volatile matter is less than 1%, and the vinyl content is 0.03 to 0.06%.
[0012] In one embodiment of the present application, the M / Q of the MQ resin is 0.6-1.0, and the hydroxyl content is 0.1-1.5%.
[0013] In one embodiment of the present application, the organic solvent is a non-polar small molecule solvent, preferably one or more of hexamethyldisiloxane, ethyl acetate, benzene, toluene, and xylene.
[0014] In one embodiment of the present application, the linear polymer silicone oil containing vinyl functional groups is a vinyl-terminated silicone oil, preferably having a viscosity of 10,000 to 100,000 cP at 25°C.
[0015] In one embodiment of the present application, the general structural formula of the branched polymer containing vinyl functional groups is as follows:
[0016]
[0017] Where n and t are each a natural number between 1 and 200, R 1 , R 2 They are each optionally selected from aliphatic hydrocarbon groups below C4 and alicyclic groups of C5-6, preferably methyl, ethyl, propyl, isopropyl, butyl, 3,3,3-trifluoropropyl, cyclopentyl, cyclohexyl and phenyl; preferably, the branched polymer containing vinyl functional groups has a vinyl content of 0.1-1%; preferably, the branched polymer containing vinyl functional groups has a viscosity of 20-600 cP at 25°C.
[0018] In one embodiment of the present application, the vinyl functional group-containing organosilicon monomer is a difunctional small molecule vinyl siloxane, preferably one or more of divinyldimethoxysilane, divinyldiethoxysilane, tetramethyldivinyldisiloxane, and divinylhexamethyltrisiloxane.
[0019] In one embodiment of the present application, the hydrogen content of the hydrogen-containing silicone oil is 0.2-1.6%, and the viscosity is 10-100 cP at 25°C.
[0020] Another object of the present invention is to provide a branched polymer containing vinyl functional groups.
[0021] A branched polymer containing vinyl functional groups, wherein the branched polymer is the branched polymer used in the above-mentioned pressure-sensitive adhesive, and the general structural formula of the branched polymer containing vinyl functional groups is as follows:
[0022]
[0023] Where n and t are each a natural number between 1 and 200, R 1 , R 2 They are each optionally selected from aliphatic hydrocarbon groups below C4 and alicyclic groups of C5-6, preferably methyl, ethyl, propyl, isopropyl, butyl, 3,3,3-trifluoropropyl, cyclopentyl, cyclohexyl and phenyl; preferably, the branched polymer containing vinyl functional groups has a vinyl content of 0.1-1%; preferably, the branched polymer containing vinyl functional groups has a viscosity of 20-600 cP at 25°C.
[0024] Another object of the present invention is to provide a method for preparing a branched polymer containing vinyl functional groups.
[0025] A method for preparing a branched polymer containing a vinyl functional group, wherein the branched polymer is the branched polymer used in the pressure-sensitive adhesive, or is the branched polymer mentioned above, and the method comprises the following steps:
[0026] S1: adding tetraethyl orthosilicate, hexamethyldisiloxane and tetramethyldivinyldisiloxane into a reactor, heating, adding water under acid catalyst to carry out hydrolysis reaction;
[0027] S2: adding a neutralizing agent, removing the by-product, and obtaining a vinyl branched silicone oil end-capping agent;
[0028] S3: Add octamethylcyclotetrasiloxane, vinyl branched silicone oil capping agent and acid catalyst to carry out equilibrium reaction, and obtain branched silicone oil after removing small molecules.
[0029] In one embodiment of the present application, the heating temperature in S1 is 40-120°C.
[0030] In one embodiment of the present application, the acid catalyst in S1 is one or more of trifluoromethanesulfonic acid, concentrated sulfuric acid, and acetic acid.
[0031] In one embodiment of the present application, the acid catalyst in S1 is an organic oxygen-containing acid, preferably one or more of trifluoromethanesulfonic acid, concentrated sulfuric acid, and acetic acid.
[0032] In one embodiment of the present application, the neutralizing agent in S2 is an inorganic salt, preferably one or more of sodium bicarbonate, calcium carbonate, and sodium carbonate.
[0033] In one embodiment of the present application, the acid catalyst in S3 is one or more of trifluoromethanesulfonic acid, concentrated sulfuric acid, and acetic acid. In one embodiment of the present application, the reaction temperature in S3 is 40-120°C.
[0034] Another object of the present invention is to provide a use of an aging-resistant organic silicone pressure-sensitive adhesive.
[0035] A use of an aging-resistant organic silicon pressure-sensitive adhesive, wherein the pressure-sensitive adhesive is the above-mentioned pressure-sensitive adhesive, or adopts the above-mentioned branched polymer, or adopts the branched polymer prepared by the above-mentioned method, and the pressure-sensitive adhesive is used in the field of process protective films in industrial production processes and screen shipping protective films for electronic digital products.
[0036] Compared with the prior art, the positive effects of the present invention are:
[0037] (1) In the application scenario where the adhesion range is 0 to 100 g / inch, the adhesion climbing rate of the silicone pressure-sensitive adhesive after high temperature and high humidity aging can reach ≤50%;
[0038] (2) The maximum crystal point size on the film surface does not exceed 100 μm, and the crystal point rate of a randomly cut 1 cm × 1 cm film observed under a 200x magnification microscope is ≤ 1000 / m 2 . BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a microscope observation picture of the film surface of Example 1. Figure 2 This is a microscope observation picture of the film surface of Comparative Example 1. DETAILED DESCRIPTION
[0040] The present invention is further described below by means of specific examples. The examples described in the present invention are only used to illustrate the present invention and do not limit the scope of the present invention.
[0041] The other main raw materials used in the following examples of the present invention are as follows:
[0042] Vinyl-terminated raw rubber: Hesheng Silicon Industry, 110-0, molecular weight 450,000, vinyl content 0.06%, volatile matter <1%; Hesheng Silicon Industry, 110-0, molecular weight 650,000, vinyl content 0.04%, volatile matter <1%; Hesheng Silicon Industry, 110-0, molecular weight 850,000, vinyl content 0.03%, volatile matter <1%.
[0043] Vinyl-terminated silicone oil, Zhejiang Runhe; RH-Vi301, viscosity 100000cP, RH-Vi360, viscosity 60000cP, RH-Vi302, viscosity 20000cP, RH-Vi303, viscosity 10000cP;
[0044] Divinyldimethoxysilane, Quzhou Jiancheng, purity>99%;
[0045] High hydrogen silicone oil RH202-30, viscosity 30cP, Zhejiang Runhe; Side hydrogen silicone oil RH-H512, hydrogen content 1.2%, viscosity 60cP; Side hydrogen silicone oil RH-H510, hydrogen content 1.0%, viscosity 15cP;
[0046] Tetramethyldivinyldisiloxane, Quzhou Jiancheng, purity>99%;
[0047] Hexamethyldisiloxane, purity>99%, Zhejiang Runhe;
[0048] Trifluoromethanesulfonic acid, Aladdin, purity >99%;
[0049] Octamethylcyclotetrasiloxane, Hengyecheng, purity>98%;
[0050] Methyl MQ resin xylene solution, Chenfei Technology CF 808;
[0051] Custer platinum catalyst, CAT-Pt050, Jiangsu Kexing New Materials Co., Ltd.
[0052] Branched vinyl silicone oil, DY-V411, Shandong Dayi.
[0053] Calcium carbonate, analytical grade, MacLean;
[0054] Sodium bicarbonate, analytical grade, MacLean;
[0055] Acetic acid, analytical grade, MacLean.
[0056] The main test methods involved in the following embodiments of the present invention are as follows:
[0057] (1) Pressure-sensitive adhesive adhesion test includes reference standard GB / T 2792-2014.
[0058] (2) Aging and heat resistance test method: According to the adhesion test method of GB / T 2792-2014, the pressure-sensitive adhesive tape was attached to a steel plate and placed in an oven at 60% humidity and 70°C for aging for 3 days. After being taken out and cooled, the adhesion was then tested.
[0059] (3) Randomly cut 20 1×1 cm square pieces from a 210 mm×297 mm film sample, place them on a glass slide, and place them under an optical microscope. Observe the size of the crystal points on the film surface at a magnification of 1000 times, and record the average number of crystal points as n. Calculate the crystal point rate (number / m 2 ).
[0060] The test instrument models are as follows:
[0061] Viscometer: Brookfield RV, 21# rotor, 25°C, 100 rpm;
[0062] Titrator: Mettler E38 automatic titrator;
[0063] NMR instrument: ASCEND 600M;
[0064] Adhesion: Kejian KJ-1065C tape peeling force tester;
[0065] Optical microscope: OLYMPUS CX23 biological microscope.
[0066] Preparation Example 1
[0067] Branched vinyl silicone oil was synthesized according to the following method:
[0068] 45.00 g of ethyl orthosilicate and 45.30 g of tetramethyldivinyldisiloxane were added to a three-necked flask, preheated to 60° C. under a nitrogen atmosphere, 85 μL of trifluoromethanesulfonic acid was added, stirring was continued for 2 h, 9.01 g of deionized water was slowly added dropwise, the reaction was continued for 3 h, 20.00 g of calcium carbonate was added to neutralize the trifluoromethanesulfonic acid, stirring was continued for 1 h and then filtered, and by-product ethanol and water in the system were removed by reduced pressure distillation at 60° C. and 10 mbar for 2 h to obtain a branched silicone oil capping agent 1 with a vinyl content of 22.8%.
[0069] 1288.02g of octamethylcyclotetrasiloxane, 50.05g of the above-mentioned branched silicone oil end-capping agent 1, and 1.54g of trifluoromethanesulfonic acid were added to the system, and the equilibrium reaction was continued at 55°C for 6h, and then 30.89g of calcium carbonate was added and stirred for 1h. After filtration, small molecules were removed at 60°C and 10mbar to obtain branched vinyl silicone oil A1311.31g. The vinyl content was measured by chemical titration to be 0.50%. In its structure, n=8, t=1, R 2 , R 3 It is methyl.
[0070] Product characterization:
[0071] Vinyl content: 0.50%, viscosity: 446 cP.
[0072] Nuclear magnetic data 29Si NMR (80MHz, CDCl 3 ): [d, ppm] = -4.15CH 2 CH-Si(CH 3 ) 2 -O-, -22.02(-Si(CH 3 ) 2 -O-), -108.01(-Si-(O-Si-) 4 ).
[0073] Preparation Example 2
[0074] 45.00 g of ethyl orthosilicate and 80.53 g of tetramethyldivinyldisiloxane were added to a three-necked flask, preheated to 100° C. under a nitrogen atmosphere, 0.5 g of acetic acid was added, stirring was continued for 2 h, 15.38 g of deionized water was slowly added dropwise, the reaction was continued for 3 h, 40.00 g of sodium bicarbonate was added to neutralize trifluoromethanesulfonic acid, stirring was continued for 1 h and then filtered, and by-product ethanol and water in the system were removed by reduced pressure distillation at 60° C. and 10 mbar for 2 h to obtain a branched silicone oil capping agent 2 with a vinyl content of 11.7%.
[0075] 1248.95g of octamethylcyclotetrasiloxane, 67.25g of the above-mentioned branched silicone oil end-capping agent 2, and 1.52g of trifluoromethanesulfonic acid were added to the system, and the equilibrium reaction was continued at 55°C for 6h, and then 30.89g of calcium carbonate was added and stirred for 1h. After filtration, small molecules were removed at 60°C and 10mbar to obtain 1289.88g of branched vinyl silicone oil B. The vinyl content was 0.24% and the viscosity was 197cP measured by chemical titration. In its structure, n=1, t=150, R 2 , R 3 It is methyl.
[0076] Preparation Example 3
[0077] 1467.21g of octamethylcyclotetrasiloxane, 77.42g of the branched silicone oil end-capping agent 1 in Preparation Example 1, and 1.78g of trifluoromethanesulfonic acid were added to a three-necked flask, and the equilibrium reaction was continued at 60°C for 10h, and then 44.50g of calcium carbonate was added and stirred for 1h. The mixture was filtered and small molecules were removed at 100°C and 50mbar to obtain branched vinyl silicone oil C1513.73g. The vinyl content was 0.19% and the viscosity was 540cp by chemical titration. In the structure, n=8, t=90, R 2 is trifluoropropyl, R 3 It is methyl.
[0078] Preparation Example 4
[0079] 850.03 g of octamethylcyclotetrasiloxane, 65.77 g of the branched silicone oil end-capping agent 2 in Preparation Example 1, and 1.06 g of trifluoromethanesulfonic acid were added to a three-necked flask, and the equilibrium reaction was continued at 70 ° C for 4 h, and then 31.80 g of calcium carbonate was added and stirred for 1 h. After filtration, small molecules were removed under 80 ° C and 10 mbar to obtain branched vinyl silicone oil D897.49 g. The vinyl content was measured by chemical titration to be 0.68%, and the viscosity was 35 cP. In its structure, n = 1, t = 20, R 2 , R 3 It is phenyl.
[0080] Example 1
[0081] 34.29 g CF 808MQ resin xylene solution and 28 g 110-0 methyl vinyl rubber with a molecular weight of 65w were added to the reactor, and the mixture was kept warm at 40°C and stirred for 2 h. Then, 33.48 g 2w viscosity terminal vinyl silicone oil RH-Vi302, 0.4 g divinyldimethoxysilane, 8.98 g branched vinyl silicone oil A with a vinyl content of 0.5%, and 0.33 g high hydrogen silicone oil RH202-30 (hydrogen content 1.6%) were added and stirred for 2 h to obtain a pressure-sensitive adhesive product.
[0082] After adding 30.71g xylene solvent and 0.18g CAT-Pt050, stir at room temperature for 1h, and then apply film (substrate is 38μm PET), and cure at 150℃ for 2min. The film thickness is 17μm. After 24h of lamination, the initial peel force is 12.6g / inch. After aging in an oven at 70℃ and 60RH% for 3d, the peel force is 17.9g / inch, and the aging climbing rate is 42%. The calculated crystal point rate of the film surface is 500 / m 2 .
[0083] Example 2
[0084] 50.68 g of MQ resin CF 808 xylene solution and 50 g of 110-0 methyl vinyl rubber with a molecular weight of 45w were added to the reactor, and the mixture was kept at 50°C and stirred for 2 h. Then, 52.93 g of 6w viscosity terminal vinyl silicone oil RH-Vi360, 1.63 g of tetramethyl divinyl disiloxane, 27.69 g of branched vinyl silicone oil B with a vinyl content of 0.24%, and 1.36 g of side hydrogenated silicone oil RH-H510 (hydrogen content 1.0%) were added and stirred for 2 h to obtain a pressure-sensitive adhesive product. After adding 54.29g of solvent ethyl acetate and 0.39g of Custer catalyst CAT-Pt050, stirring was continued at room temperature for 1h, and then the film was coated (the substrate was 50μm PET), and cured at 150℃ for 2min, and the film thickness was 17μm; after 24h of lamination, the initial peeling force was measured to be 13.7g / inch, and after aging in an oven at 70℃ and 60RH% for 3d, the peeling force was measured to be 15.5g / inch, the aging climbing rate was 13%, and the calculated film surface crystal point rate was 500 / m 2 .
[0085] Example 3
[0086] 77.96 g of MQ resin CF-808 xylene solution and 34 g of 110-0 methyl vinyl rubber with a molecular weight of 85w were added to the reactor, and the mixture was kept at 50°C and stirred for 2 h. Then, 19.8 g of 6w viscosity terminal vinyl silicone oil, 1.63 g of divinyldiethoxysilane, 33.94 g of branched vinyl silicone oil D with a vinyl content of 0.68%, and 1.13 g of side hydrogenated silicone oil (hydrogen content of 1.2%) were added, and stirring was continued for 2 h to obtain a pressure-sensitive adhesive product. After adding 29.43g hexamethyldisiloxane solvent and 0.28g CAT-Pt050, stir at room temperature for 1h, and then apply film (substrate is 50μm PET), and cure at 150℃ for 2min, the film thickness is 17μm; the initial peel force is 15.1g / inch after 24h of bonding, and the peel force is 22.3g / inch after aging in an oven at 70℃ and 60RH% for 3d, the aging climbing rate is 48%, and the calculated film surface crystal point rate is 1000 / m 2 .
[0087] Example 4
[0088] 98.60 g of MQ resin xylene solution SH-5201S and 77 g of 110-0 methyl vinyl raw rubber with a molecular weight of 65w were added to the reactor, and the mixture was kept at 50°C and stirred for 2 h. Then, 33.90 g of 1w viscosity terminal vinyl silicone oil RH-Vi303, 4.84 g of divinyldiethoxysilane, 58.11 g of branched vinyl silicone oil A with a vinyl content of 0.50%, and 1.94 g of high hydrogen silicone oil RH202-30 (hydrogen content 1.6%) were added, and the mixture was stirred for 2 h to obtain a pressure-sensitive adhesive product. After adding 50.73g xylene solvent and 0.49g CAT-Pt050, stir at room temperature for 1h, and then apply film (substrate is 50μm PET), and cure at 150℃ for 2min. The film thickness is 17μm. After 24h of bonding, the initial peel force is 10.8g / inch. After aging in an oven at 70℃ and 60RH% for 3d, the peel force is 15.1g / inch. The aging climbing rate is 40%, and the calculated film surface crystal point rate is 500 / m 2 .
[0089] Example 5
[0090] 195.71 g of MQ resin SH-5201S xylene solution and 156 g of 110-0 methyl vinyl rubber with a molecular weight of 65w were added to the reactor, and the mixture was kept at 50°C and stirred for 2 h. Then, 116.22 g of 1w viscosity terminal vinyl silicone oil 1w-RH-Vi301, 3.87 g of divinyldiethoxysilane, 48.34 g of branched vinyl silicone oil A with a vinyl content of 0.50%, and 1.4 g of high hydrogen silicone oil RH202-30 (hydrogen content 1.6%) were added, and stirring was continued for 2 h to obtain a pressure-sensitive adhesive product. After adding 41.29g xylene solvent and 0.93g CAT-Pt050, the mixture was stirred at room temperature for 1h, and then coated (the substrate was 50μm PET). The mixture was cured at 150°C for 2min, and the film thickness was 17μm. After 24h of lamination, the initial peeling force was 11.3g / inch. After aging in an oven at 70°C and 60RH% for 3d, the peeling force was 16.4g / inch. The aging climbing rate was 45%, and the calculated film surface crystal point rate was 1000 / m 2 .
[0091] Example 6
[0092] 214.29 g of MQ resin MSR8808 xylene solution and 200 g of 110-0 methyl vinyl rubber with a molecular weight of 65w were added to the reactor, and the mixture was kept at 50°C and stirred for 2 h. Then, 133.07 g of 10w viscosity terminal vinyl silicone oil RH-Vi301, 4.44 g of divinyldiethoxysilane, 55.35 g of branched vinyl silicone oil A with a vinyl content of 0.50%, and 1.61 g of high hydrogen silicone oil (hydrogen content of 1.6%) were added, and the mixture was stirred for 2 h to obtain a pressure-sensitive adhesive product. After adding 35.71g xylene solvent and 1.09g CAT-Pt050, stir at room temperature for 1h, and then coat the film (the substrate is 50μm PET). Curing at 150℃ for 2min, the film thickness is 17μm; after 24h of lamination, the initial peel force is 6.9g / inch, and after aging in an oven at 70℃ and 60RH% for 3d, the peel force is 9.7g / inch, the aging climbing rate is 41%, and the calculated film surface crystal point rate is 500 / m 2 .
[0093] Example 7
[0094] 285.71 g of MQ resin MSR8808 xylene solution and 189 g of 110-0 methyl vinyl rubber with a molecular weight of 65w were added to the reactor, and the mixture was kept warm at 40°C and stirred for 2 h. Then, 159.39 g of 6w viscosity terminal vinyl silicone oil 6w-RH-Vi360, 1.16 g of tetramethyl divinyl disiloxane, 70.46 g of branched methyl vinyl silicone oil C with a vinyl content of 0.19%, and 1.93 g of side hydrogenated silicone oil RH-H512 with a hydrogen content of 1.2% were added and stirred for 2 h to obtain a pressure-sensitive adhesive product. After adding 64.29g xylene solvent and 1.24g CAT-Pt050, stir at room temperature for 1h, and then apply film (substrate is 50μm PET), and cure at 150℃ for 2min. The film thickness is 17μm. After 24h of lamination, the initial peel force is 12.6g / inch. After aging in an oven at 70℃ and 60RH% for 3d, the peel force is 18.3g / inch. The aging climbing rate is 45%, and the calculated film surface crystal point rate is 500 / m 2 .
[0095] Comparative Example 1
[0096] Compared with Example 1, the only difference is that the branched polymer described in the present invention is not added.
[0097] Add 34.29g of mqCF-808 resin xylene solution and 28g of 110-0 methyl vinyl rubber with a molecular weight of 65w into the reactor, keep warm at 40°C and stir for 2h, then add 39.46g of 2w viscosity terminal vinyl silicone oil RH-Vi302, 0.4g of divinyldimethoxysilane and 0.33g of high hydrogen silicone oil RH202-30 (hydrogen content 1.6%) and continue stirring for 2h to obtain a pressure-sensitive adhesive product. After adding 30.71g xylene solvent and 0.18g CAT-Pt050, the mixture was stirred at room temperature for 1h, and then coated (substrate was 38μm PET), and cured at 150℃ for 2min. The film thickness was 17μm. After 24h of lamination, the initial peeling force was 14.4g / inch. After aging in an oven at 70℃ and 60RH% for 3d, the peeling force was 26.9g / inch. The aging climbing rate was 87%, and the calculated film surface crystal point rate was 9500 / m 2 .
[0098] Comparative Example 2
[0099] Compared with Example 1, the only difference is that the branched polymer described in the present invention is not added, and the commercially available branched silicone oil DY-V411 of the same mass is added.
[0100] 34.29 g of MQ resin CF-808 xylene solution and 28 g of methyl vinyl raw rubber with a molecular weight of 65W were added to the reactor, and the mixture was kept warm at 40°C and stirred for 2 h. Then, 33.48 g of 2w viscosity terminal vinyl silicone oil RH-Vi302, 0.4 g of divinyldimethoxysilane, 8.98 g of branched vinyl silicone oil DY-V411, and 0.33 g of high hydrogen silicone oil RH202-30 (hydrogen content 1.6%) were added and stirred for 2 h to obtain a pressure-sensitive adhesive product. After adding 30.71g xylene solvent and CAT-Pt050, stir at room temperature for 1h, and then coat the film (substrate is 38μm PET), and cure at 150℃ for 2min. The film thickness is 17μm. After 24h of lamination, the initial peeling force is 15.1g / inch. After aging in an oven at 70℃ and 60RH% for 3d, the peeling force is 33.8g / inch. The aging climbing rate is 124%, and the calculated film surface crystal point rate is 6500 / m 2 .
[0101]
[0102] It can be seen from Comparative Examples 1 and 2 that the aging climb of the addition-type pressure-sensitive adhesive without the special structure branched vinyl silicone oil in this application and the film surface crystal point rate are significantly improved in Examples 1 to 6.
[0103] Those skilled in the art will appreciate that, based on the teachings of this specification, some modifications or adjustments may be made to the present invention, and these modifications or adjustments should also be within the scope defined by the claims of the present invention.
Claims
1. An aging-resistant silicone pressure-sensitive adhesive, characterized in that: The pressure-sensitive adhesive comprises the following components in parts by mass:
2. The pressure-sensitive adhesive according to claim 1, characterized in that: The molecular weight of the vinyl-terminated raw rubber is 450,000 to 850,000, the volatile matter is less than 1%, and the vinyl content is 0.03 to 0.06%; and / or, the M / Q of the MQ resin is 0.6 to 1.0, and the hydroxyl content is 0.1 to 1.5%; And / or, the organic solvent is a non-polar small molecule solvent, preferably one or more of hexamethyldisiloxane, ethyl acetate, benzene, toluene, xylene, etc.; And / or, the linear polymer silicone oil containing vinyl functional groups is a vinyl-terminated silicone oil, preferably having a viscosity of 10,000 to 100,000 cP at 25°C.
3. The pressure-sensitive adhesive according to claim 1 or 2, characterized in that: The general structure formula of the branched polymer containing vinyl functional groups is as follows: wherein n and t are each selected from a natural number of 1 to 200, R1 and R2 are each selected from a C4 or lower aliphatic hydrocarbon group and a C5-6 alicyclic group, preferably a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a 3,3,3-trifluoropropyl group, a cyclopentyl group, a cyclohexyl group, and a phenyl group; Preferably, the vinyl content of the branched polymer containing vinyl functional groups is 0.1 to 1%; Preferably, the branched polymer containing vinyl functional groups has a viscosity of 20-600 cP at 25°C.
4. The pressure-sensitive adhesive according to any one of claims 1 to 3, characterized in that: The vinyl functional group-containing organosilicon monomer is a difunctional small molecule vinyl siloxane, preferably one or more of divinyldimethoxysilane, divinyldiethoxysilane, tetramethyl divinyldisiloxane, and divinylhexamethyltrisiloxane; And / or, the hydrogen content of the hydrogen-containing silicone oil is 0.2-1.6%, and the viscosity is 10-100 cP at 25°C.
5. A branched polymer containing vinyl functional groups, wherein the branched polymer is the branched polymer used in the pressure-sensitive adhesive according to any one of claims 1 to 4, characterized in that: The general structure formula of the branched polymer containing vinyl functional groups is as follows: wherein n and t are each selected from a natural number of 1 to 200, R1 and R2 are each selected from a C4 or lower aliphatic hydrocarbon group and a C5-6 alicyclic group, preferably a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a 3,3,3-trifluoropropyl group, a cyclopentyl group, a cyclohexyl group, and a phenyl group; Preferably, the vinyl content of the branched polymer containing vinyl functional groups is 0.1 to 1%; Preferably, the branched polymer containing vinyl functional groups has a viscosity of 20-600 cP at 25°C.
6. A method for preparing a branched polymer containing vinyl functional groups, wherein the branched polymer is the branched polymer used in the pressure-sensitive adhesive according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: S1: adding tetramethyl divinyl disiloxane tetraethyl orthosilicate into a reactor, heating, adding water under acid catalyst to carry out hydrolysis reaction; S2: adding a neutralizing agent, removing the by-product, and obtaining a vinyl branched silicone oil end-capping agent; S3: Add octamethylcyclotetrasiloxane, vinyl branched silicone oil capping agent and acid catalyst to carry out equilibrium reaction, and obtain branched silicone oil after removing small molecules.
7. The method according to claim 6, characterized in that The heating temperature in S1 is 40 to 120°C; and / or, the acid catalyst in S1 is an organic oxygen-containing acid, preferably one or more of trifluoromethanesulfonic acid, concentrated sulfuric acid, and acetic acid; and / or, the neutralizing agent in S2 is an inorganic salt, preferably one or more of sodium bicarbonate, calcium carbonate, and sodium carbonate; and / or, the acid catalyst in S3 is an organic oxygen-containing acid, preferably one or more of trifluoromethanesulfonic acid, concentrated sulfuric acid, and acetic acid; And / or, the reaction temperature in S3 is 40 to 120°C.
8. Use of an aging-resistant organosilicon pressure-sensitive adhesive, wherein the pressure-sensitive adhesive is the pressure-sensitive adhesive described in any one of claims 1 to 4, or the branched polymer described in claim 5, or the branched polymer prepared by the method described in claim 6 or 7, and the pressure-sensitive adhesive is used in the field of process protective films in industrial production processes and screen shipping protective films for electronic digital products.
Citation Information
Patent Citations
Organopolysiloxane composition and preparation method thereof and semiconductor device
CN107629460A
Curable polyorganosiloxane composition, and polyorganosiloxane cured product
CN113242885A
Organosilicon pressure-sensitive adhesive for fingerprint-resistant glass as well as preparation method and application of organosilicon pressure-sensitive adhesive
CN113956833A
Ultralow-adhesive-force and low-climbing organic silicon pressure-sensitive adhesive as well as preparation method and application thereof
CN114958295A
In situ low temperature siloxane gel
US4709001A
Cited By
UV protective film and preparation method thereof
CN121471826A